Comparative structural response of two steel bridges constructed 100 years apart - Varum, Humberto (2013)
This paper presents a comparative numerical analysis of the structural behaviour and seismic performance of two existing steel bridges, the Infiernillo II Bridge and the Pinhao Bridge, one located in Mexico and the other in Portugal. The two bridges have similar general geometrical characteristics, but were constructed 100 years apart. Three-dimensional structural models of both bridges are developed and analysed for various load cases and several seismic conditions. The results of the comparative analysis between the two bridges are presented in terms of natural frequencies and corresponding vibration modes, maximum stresses in the structural elements and maximum displacements. The study is aimed at determining the influence of a 1 century period in material properties, transverse sections and expected behaviour of two quite similar bridges. In addition, the influence of the bearing conditions in the global response of the Pinhao Bridge was evaluated.